STRATEGI GURU PAI DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL SISWA KELAS VI SD - Marisca Oktaria; Karoma Karoma (PAI RAFAH, 2019)
Teacher strategies in the learning process that are less precise can cause students to be inactive and focused in learning, students are less enthusiastic and some students are noisy in the classroom. This is because teachers pay more attention to students 'intellectual intelligence and pay less attention to students' emotional intelligence in learning activities. The purpose of this study was to determine the emotional intelligence of Grade VI students in Palembang 214 Public Elementary School and to find out the PAI teacher's strategy in developing the emotional intelligence of Grade VI students in Palembang 214 Public Elementary School. The research method used is descriptive qualitative analysis that discusses the PAI teacher's strategy in developing emotional intelligence of grade VI students in 214 Negeri SD Palembang. The type of approach used in this research is descriptive qualitative with data collection techniques through observation, interviews, documentation and triangulation. Analysis of data qualitatively through three stages, namely data reduction, data presentation and conclusion stages. The results of this study that the PAI Teacher Strategy in Developing Emotional Intelligence of Class VI Students at 214 Public Elementary Schools in Palembang. First, learning includes interactive activities, namely the existence of good lead in learning. Inspirational, which is to let students act and think according to their inspiration. The fun that can be created from a neat and attractive room arrangement. Challenging, namely learning must develop students' curiosity. Motivation, which is to give appreciation and encourage students' interest in learning. Second, emotional intelligence possessed by students includes self-awareness, ie students can recognize their emotions. Self control, which is able to express feelings. Motivation, which has a desire to achieve goals. Empathy, namely students can understand the feelings of others. And social abilities, which are able to interact well.